Upaya Meningkatkan Kompetensi Guru di Sekolah TK Maulana Nusantara terhadap Hasil Belajar Anak - Hilda Zahra Lubis; Wildani Wildani; Tiara Winanda; Risa Ummah Pratiwi; Anti Pebriani Syahpitri; Zahra Yunita; Irma Qurata Aini; Siti Halisah; Zulham Efendi Marpaung (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
A nation has a responsibility to improve the quality of its human resources. Human capital is the primary investment in development in order to improve community life. This study employs quantitative descriptive research as the method of inquiry. According to the findings of the research, the teacher's strategy for increasing early childhood learning motivation in MAULANA NUSANTARA Kindergarten consists of explaining the advantages of learning, presenting fun learning, specifically learning through play, using educational game tools, allowing children to express their opinions and ideas without requiring them to agree with the teacher, always providing assistance to children, providing real learning experiences, schools holding meetings with students' parents, and teachers awarding students. giving praise or flattery, stars, merchandise, thumbs up, and the chance to travel home for the first time. Keywords: Competence, teacher, students